Mitochondria-targeted antioxidant peptide SS-31 mediates neuroprotection in a rat experimental glaucoma model. (28th February 2019) - Wu, Xiaoqiong; Pang, Yu; Zhang, Zhilin; Li, Xiabin; Wang, Chao; Lei, Yingqing; Li, Ailing; Yu, Ling; Ye, Jian
Abstract: To investigate the neuroprotective effects of the mitochondria-targeted antioxidant Szeto-Schiller peptide 31 (SS-31) in a rat experimental glaucoma model, SS-31 was intraperitoneally (IP) injected into Sprague-Dawley rats, followed by intracameral injection of polystyrene microspheres to induce elevated intraocular pressure (IOP). After 6 weeks, electroretinography (ERG) and flash visual-evoked potentials (F-VEPs) were recorded to assess retinal function. Hematoxylin–eosin staining was performed on retinal cross-sections to measure ganglion cell complex (GCC) thickness. Apoptotic retinal cells were assessed by TUNEL staining. Brn3a-positive retinal ganglion cells (RGCs) were counted in retinal flat mounts via immunofluorescence. The retinal total SOD, SOD2, and MDA expression levels were assessed in retinal tissue homogenates. The cyt c, Bax, and Bcl-2 protein levels in rat retinas were detected by western blot analysis. Bax and Bcl-2 expressions were also evaluated using immunohistochemistry in paraffinized sections. Our results showed that the rats that received microsphere injection developed elevated IOP. SS-31 ameliorated the reductions in the a- and b-wave amplitudes on ERG and the F-VEP amplitude in glaucomatous eyes. GCC thickness was preserved, TUNEL-positive cells were decreased in the retina, and Brn3a-positive RGCs were increased in the SS-31-treated glaucoma group compared with those in the non-treated glaucoma group. SS-31 significantly reduced MDA levels and increased SOD2 levels after glaucoma induction. Significant suppression of cyt c release, upregulation of Bcl-2, and downregulation of Bax were observed following SS-31 administration. In summary, SS-31 exerts neuroprotective effects in this experimental glaucoma model by inhibiting mitochondrial dysfunction and therefore represents a promising therapeutic agent for glaucoma.